FEATURES OF THE FIRST STAGE OF FOREIGN LANGUAGE TEACHING TO PRIMARY COMPREHENSIVE SCHOOL PUPILS - Олена Паршикова (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The article determines objects, aims, tasks and features of teaching a foreign language at thе first stage of primary comprehensive school. Learning a foreign language on the first adaptation phase (first and second forms) is mostly receptive, imitative and reproductive, because the main method of language acquisition among six and seven-year-old pupils is imitation and the mechanisms of speech are perception, understanding and reproduction of speech units by means of imitation, choice and actualization. Expediency of the application of nature-conforming communicative-playing methods for the realization of these mechanisms of foreign language communication, in particular of such its initial types as quasi- and protocommunication, is substantiated, examples of these methods application in the German language textbooks for the pupils of the first and second forms of the primary comprehensive school are demonstrated.